2019
DOI: 10.1503/cjs.012018
|View full text |Cite
|
Sign up to set email alerts
|

Association between socioeconomic deprivation and surgical complications in adults undergoing ankle fracture fixation: a population-based analysis

Abstract: Background: Few studies have investigated the outcomes of surgical fracture care among socially deprived patients despite the increased incidence of fractures and the inequality of care received in this group. We evaluated whether socioeconomic deprivation affected the complications and subsequent management of marginalized/homeless patients following surgery for ankle fracture. Methods:In this retrospective, population-based cohort study involving 202 hospitals in Ontario, Canada, we evaluated 45 444 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Conversely, homeless patients were significantly less likely to have their hardware removed in isolation, potentially resulting from unequal provision of care at the patient level or a lack of follow-up. 14,25 These findings contribute to the growing body of evidence that demonstrates the significant impact of social determinants of health disparities on ankle fracture surgery, 7,8 and surgical fracture care more broadly. 9–14 However, it should be noted that rates of amputation, irrigation and debridement, and repeat ORIF were still quite low even in the homeless cohort.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Conversely, homeless patients were significantly less likely to have their hardware removed in isolation, potentially resulting from unequal provision of care at the patient level or a lack of follow-up. 14,25 These findings contribute to the growing body of evidence that demonstrates the significant impact of social determinants of health disparities on ankle fracture surgery, 7,8 and surgical fracture care more broadly. 9–14 However, it should be noted that rates of amputation, irrigation and debridement, and repeat ORIF were still quite low even in the homeless cohort.…”
Section: Discussionmentioning
confidence: 71%
“…Recent findings highlight the considerable impact of social determinants of health disparities on orthopedic trauma surgery. [7][8][9][10][11][12][13] However, to our knowledge, only one study has directly explored surgical outcomes in homeless patients with orthopedic trauma. 14 Given that musculoskeletal injury is a substantial cause of disability, understanding disparities in outcomes for homeless patients following surgical fracture care may help develop interventions that promote health equity.…”
Section: Introductionmentioning
confidence: 99%
“…26,38 With respect to complications, two studies reported high rates of treatment failure and amputation for orthopedic injuries, including open reduction and internal fixation for ankle fracture and foot osteomyelitis. 40,47 A study by Titan et. al.…”
Section: Domain 3: Post-operative Carementioning
confidence: 99%
“…The assessment of limb salvage vs. amputation begins with early, thoughtful, and, when possible, shared decision making with the patient and/or family to either amputate a threatened limb or begin a pathway of limb salvage. The possibility of a failed limb salvage resulting in delayed amputation due to infection, compartment syndrome, flap failure, nonunion, unsatisfactory function, or pain must be discussed to set treatment expectations [15][16][17] . Access to post-operative care, a stable living situation, self-efficacy and engagement in care, and social support should be considered [18] .…”
Section: Can and Should The Limb Be Salvaged?mentioning
confidence: 99%